Incidence and distribution of coeliac disease in Campania (Italy): 2011–2013 - Zingone, Fabiana; West, Joe; Auricchio, Renata; Maria Bevilacqua, Rosa; Bile, Guido; Borgheresi, Patrizia; Erminia Bottiglieri, Maria; Caldore, Mariano; Capece, Giuseppe; Cristina Caria, Maria; Crudele, Antonio; Cuomo, Rosario; et al. (SAGE, 2015)
BACKGROUND: There exists a wide variation in the reported incidence of coeliac disease in recent decades. We aimed to evaluate the incidence rate of coeliac diagnoses performed in an Italian region, Campania, between 2011 and 2013 and its variation therein.